Correction: Meta-transcriptome Profiling of the Human-Leishmania braziliensis Cutaneous Lesion. - Stephen M Christensen; Laura A L Dillon; Lucas P Carvalho; Sara Passos; Fernanda O Novais; V Keith Hughitt; Daniel P Beiting; Edgar M Carvalho; Phillip Scott; Najib M El-Sayed; David M Mosser (PLOS Neglected Tropical Diseases, 2017)
[This corrects the article DOI:10.1371/journal.pntd.0004992.].